PENGGUNAAN TEPUNG GLUKOMANAN UMBI GEMBILI (Dioscorea esculenta L.) SEBAGAI BAHAN TAMBAHAN MAKANAN PADA PENGOLAHAN SOSIS DAGING AYAM - Herlina Herlina; Ikhlas Darmawan; Andrew Setiawan Rusdianto (Faculty of Agricultural Technology, University of Jember, 2015)
Gembili tuber contains 2,9% of glucomannan and potentially as food additive in chicken sausage processing. The purpose of this study was to determine the amount of the gembili’s glucomannan addition on the physical, chemical and organoleptic characteristics of chicken sausage and knowing the amount of the gembili's glucomannan flour addition on chicken sausage processing and to produce sausage with a good characteristics and panelists preferred. The study was designed using completely randomized design with one factor and three replications. Parameter research includes characterization of gembili's glucomannan flour (brightness, WHC, ash content, protein content, moisture content, and the levels of glucomannan), brightness, texture, ash content, moisture content, protein content, fat content, the organoleptic properties, and effectiveness test to determine the best treatment. The results showed that the addition of gembili's glucomannan flour significantly affect the texture, moisture content, and organoleptic. But did not significantly affect the fat content, protein content, brightness, and ash content. Effectiveness test showed that the value of the highest combination of all parameters are in sausage meat chicken with the addition of 0.3% gembili's glucomannan flour with the analysis results that the brightness of 51.96, the texture of 75.57 g / mm, ash content of 1.41%, 1,78% WHC, levels water 52.13%, 16.47% protein content, fat content 8.84%, the organoleptic properties of flavor 3.88, 3.68 organoleptic properties of color, the organoleptic properties of elasticity of 3.64%, the organoleptic properties of the slices appearance of 3.92, and the nature of the overall preferences of 3.88.Keywords: food additive, gembili tuber, glucomannan, addition variation